GIS Flood Prone Agricultural Land East Java Using Multi-Method Attribute Utility Theory - Mala Rosa Aprillya; Uswatun Chasanah (Universitas Bumigora, 2022)
East Java has various regional conditions. The condition of the area certainly has the potential for disasters that have a significant impact on the agricultural sector. Flood is one of the factors that damage agricultural land. Flood risk management plays an important role in guiding the government in making timely and appropriate decisions for flood rescue and relief. The purpose of this research is a study of flood risk assessment in the agricultural sector in East Java using Multi Attribute Utility Theory. The Multi Attribute Utility Theory is used to solve problems related to spatial planning and disaster management because it is systematic and suitable for solving complex problems such as the agricultural sector. The results showed that the agricultural land areas in East Java with the category of very flood-prone include Bojonegoro, Lamongan, Tuban, and Sidoarjo Regencies. Furthermore, the results of this study were visualized by mapping flood risk using a GIS. This can be used for efforts in flood disaster management. This research is expected to assist policy making at the Department of Agriculture and Food Security in monitoring flood-prone agricultural land in order to minimize the occurrence of flood disasters in the agricultural sector.